Guess who is praying? - Abd Razak, Dzulkifli (2006)
Both the American President and the British Prime Minister have claimed that they had divine guidance to invade Iraq. THREE years after the invasion of Iraq by the socalled coalition of the willing at the instigation of the AngloAmerican leaders, the situation can be likened to a madhouse far worse than previous years. Despite claims of progress on the democratic front, the number of deaths continues to rise unabated. Only this time, the threat of sectarian war looms on the horizon, pitting the "liberated" Iraqis against each other. Even the US President was quoted as admitting that some people are "trying to sow the seeds of sectarian violence". Who that "someone" is anybody’s guess. As an indication of the worsening situation, the much revered Golden Mosque in Samarra was a target of violence and scores of people were killed last month.